2020
DOI: 10.1155/2020/9718714
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Underweight and Its Associated Factors among Reproductive Age Group Women in Ethiopia: Analysis of the 2016 Ethiopian Demographic and Health Survey Data

Abstract: Background. Underweight is defined as being below the healthy weight range. Underweight in reproductive age group women not only affects women but also increases the risk of an intergenerational cycle of malnutrition and child mortality. Various factors are linked with underweight among women. However, studies on the prevalence of underweight and its associated factors among women are limited in Ethiopia. Hence, this study aimed to assess the prevalence of underweight and its associated factors among reproduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 42 publications
1
15
0
Order By: Relevance
“…Nonetheless, this decrease may also present risks in an unintended underweight condition. Being in a severe underweight condition is associated with a series of health conditions, for instance, higher odds of developing renal pathologies as a comorbidity of diabetes type 2 [ 81 ], osteoporosis, anemia and inefficient immune system [ 82 ], or fertility issues [ 83 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, this decrease may also present risks in an unintended underweight condition. Being in a severe underweight condition is associated with a series of health conditions, for instance, higher odds of developing renal pathologies as a comorbidity of diabetes type 2 [ 81 ], osteoporosis, anemia and inefficient immune system [ 82 ], or fertility issues [ 83 ].…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, the prevalence of underweight was higher among participants with some level of education compared to those of illiterates, whereas in the other study a higher educational level was associated with a reduced risk of underweight. 36 In this study, having a fewer number of family size was associated with a higher risk of underweight. But in the other study having had a larger family size was associated with an increased risk of underweight compared to having less family size 37 In this study, good drug adherence was associated with a lower risk of underweight which was also supported by the other findings.…”
Section: Discussionmentioning
confidence: 50%
“…Accordingly, the prevalence of underweight was higher among participants with some level of education compared to those of illiterates, whereas in the other study a higher educational level was associated with a reduced risk of underweight. 36 …”
Section: Discussionmentioning
confidence: 99%
“…8,25 Studies performed in India (2019) and in Ethiopia (2020) also found that women from rural areas suffer from underweight problems. 27,29 The differences can be explained by individual-level factors (such as younger age, lower education, etc) in the rural and urban areas of the community. Moreover, women in rural areas may face food crises, inadequate health facilities, poor eating habits, and low nutritional lifestyle.…”
Section: Discussionmentioning
confidence: 99%